Southern Ocean Macrostylidae reviewed with a key to the species and new descriptions from Maud Rise - Riehl, Torben; Brandt, Angelika (Zootaxa, 2013)
The nine currently known Southern Ocean species of the asellote isopod family Macrostylidae Hansen, 1916 are reviewed. Modified diagnoses are provided. Two new species, Macrostylis matildae n. sp. and M. scotti n. sp. are formally described. M. setulosa Mezhov, 1992, and M. vinogradovae Mezhov, 1992 are redescribed. An identification key to all species is presented. Due to substantial damage and loss of type material, M. obscura (Brandt, 1992) and M. sarsi Brandt, 1992 are henceforward considered nomina dubia. DNA sequences were yielded for molecular characterization of both new species. A phylogenetic analysis shows, although from the same locality, both species are relatively distantly related. Huge divergence is discovered within Macrostylidae which casts doubt on the monotypy of the family.